OPTIMIZATION OF TEACHER PERFORMANCE MANAGEMENT FEATURE UTILIZATION USING A TRANSFORMATIONAL LEADERSHIP APPROACHAT SDN 2 PAGERWOJO, KENDAL REGENCY - Kurniawan Widhi Hartanto; Nur Farikhin; Soedjono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Teacher performance management is vital for enhancing elementary education quality, with principals playing a strategic role, particularly through transformational leadership. This study, using a qualitative approach at SDN 2 Pagerwojo, Kendal Regency, aimed to analyze the optimization of teacher performance management feature utilization via transformational leadership. Findings show that the principal's inspirational guidance, support for innovation, and focus on individual development significantly boost management effectiveness. However, challenges like teachers' limited understanding of performance indicators, resource constraints, and lack of intrinsic motivation were identified. Recommendations include strengthening academic supervision, providing systematic mentoring, increasing access to professional training, and securing government and education department support. This study suggests transformational leadership is an effective strategy for improving teacher performance management quality, and further research on technology's role and parental involvement is recommended